2019
DOI: 10.1016/j.saa.2018.12.031
|View full text |Cite
|
Sign up to set email alerts
|

Label-free optical spectroscopy for characterizing binding properties of highly sensitive nanocrystalline cellulose-graphene oxide based nanocomposite towards nickel ion

Abstract: Surface plasmon resonance (SPR) is a label-free optical spectroscopy that is widely used for biomolecular interaction analysis. In this work, SPR was used to characterize the binding properties of highly sensitive nanocrystalline cellulose-graphene oxide based nanocomposite (CTA-NCC/GO) towards nickel ion. The formation of CTA-NCC/GO nanocomposite has been confirmed by FT-IR. The SPR analysis result shows that the CTA-NCC/GO has high binding affinity towards Ni 2+ from 0.01 until 0.1 ppm with binding affinity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 76 publications
1
29
0
1
Order By: Relevance
“…As powerful analytical tools that have enjoyed widespread attention over the past two decades, SPR sensors have been developed in several configurations to detect several analytes. These sensors serve in different fields such as medical diagnostics [318][319][320][321][322], food quality [323,324], environmental protection [325][326][327][328][329][330][331] and others. SPR, a refractive index-based detection technique has emerged as a promising sensing platform for sensitive detection of NTs, especially DA due to its substantial advantages.…”
Section: Surface Plasmon Resonance Spectroscopymentioning
confidence: 99%
“…As powerful analytical tools that have enjoyed widespread attention over the past two decades, SPR sensors have been developed in several configurations to detect several analytes. These sensors serve in different fields such as medical diagnostics [318][319][320][321][322], food quality [323,324], environmental protection [325][326][327][328][329][330][331] and others. SPR, a refractive index-based detection technique has emerged as a promising sensing platform for sensitive detection of NTs, especially DA due to its substantial advantages.…”
Section: Surface Plasmon Resonance Spectroscopymentioning
confidence: 99%
“…Surface plasmon resonance (SPR) sensing. SPR measurements were conducted based on Kretschmann configuration [65][66][67][68] by evaporating Au/DSU/NH 2 rGO-PAMAM/IgM sensor film onto the prism surface. The prism was placed on an optical stage driven by a stepper motor with a resolution of 0.001° (Newport MM 3000) to let the incident light from laser beam (632.8 nm, 5 mW) pass through the prism and hits a gold layer to generate the surface plasmon waves at the interface.…”
mentioning
confidence: 99%
“…These authors reported that the developed green hybrid was efficient and had a strong regeneration performance. Recently, Daniyal et al have prepared hexadecyltrimethylammonium bromide (CTA) modified CNC/GO thin film and assessed its potential in sensing copper and nickel ions based on surface plasmon resonance (SPR) technique [157,158]. The authors initially prepared CTA-CNC solution and then 0.1 wt.% of GO was dispersed within the solution and sonicated at 70 • C for 1 h ( Figure 8B).…”
Section: Cnc/gomentioning
confidence: 99%